Fatores cr??ticos de sucesso na implanta????o da governan??a da tecnologia da informa????o na Administra????o P??blica Federal - Reis, Andr?? Luiz Nascimento (2016)
Information Technology plays an increasingly and important role in organizations. Therefore, its management efficiently and effectively promotes the achievement of organizational objectives. In Brazil, the great leverage of Information Technology Governance practices in the Federal Public Administration is the Court of the Union, which conducts a biannual assessment of entities linked to the federal government. However, the implementation of Governance of Information Technology practices in Federal Public Administration lacks objective guidelines. In this sense, this research aimed to identify Critical Success Factors in the implementation of these practices. For this research, a literature review was used for the selection of works related to the theme and extraction of Critical Success Factors. After extraction of the Critical Success Factors, experts in Information Technology Governance were consulted through the Delphi Method to indicate which critical factors are, in their perceptions, the most relevant. The factors considered relevant by the experts were presented the Information Technology managers of organizations of the Federal Public Administration to collect their perceptions of these factors in the context of the implementation of the Governance of Information Technology. As a result were identified ten Critical Success Factors that must be observed when implementing the Governance of Information Technology in the Federal Public Administration organizations. Moreover, it was verified that the identified factors are interrelated. Thus, it is intended that this list of Critical Success Factors can be observed when the implementation of the Information Technology Governance in organizations belonging to the Federal Public Administration.